Interaction of human gut microbiota and local immune system in progression of colorectal adenoma (MIMICA-1): a protocol for a prospective, observational cohort study - Valciukiene, Jurate; Lastauskiene, Egle; Laurinaviciene, Aida; Jakubauskas, Matas; Kryzauskas, Marius; Valkiuniene, Ruta Barbora; Augulis, Renaldas; Garnelyte, Ausra; Kavoliunas, Justinas; Silinskaite, Ugne; Poskus, Tomas (Frontiers in Oncology, 2025)
IntroductionThe current understanding of colorectal carcinogenesis is based on the adenoma-carcinoma sequence, where genetics, intestinal microbiota changes and local immunity shifts seem to play the key roles. Despite the emerging evidence of dysbiotic intestinal state and immune-cell infiltration changes in patients with colorectal adenocarcinoma, early and advanced adenoma as precursors of colorectal cancer, and carcinoma in situ as the following progression, are rather less studied. The newly colon-site adapted AI-based analysis of immune infiltrates is able to predict long-term outcomes of colon carcinoma. Though it could also facilitate the pathologic evaluation of precancerous lesion’s potential to progress. Therefore, the purpose of this prospective cohort study (MIMICA-1) is, firstly, to identify the intestinal microbiota and immune infiltration patterns around the normal bowel tissue, early and advanced adenoma, carcinoma in situ, and adenocarcinoma, and secondly, to analyze the immune – microbiome interplay along the steps of conventional colorectal tumorigenesis.Methods and analysesThis study aims to prospectively recruit 40 patients (10 per group) with confirmed colorectal dysplasia undergoing endoscopic polypectomy, endoscopic mucosal resection for colorectal small (≤1cm), and large (>1cm) adenoma or carcinoma in situ, or biopsy and subsequent colon resection for invasive colorectal cancer, and 10 healthy patients undergoing screening colonoscopy. Stool samples will be collected prior to bowel preparation for the analysis of fecal (luminal) microbiota composition. Biopsy specimens will be taken from the terminal ileum, right colon, left colon, and a pathological lesion in the colon (if present) to assess mucosa-associated microbiota composition and intestinal immunity response. DNA will be extracted from all samples and sequenced using the Illumina MiSeq platform. Unifrac and Bray-Curtis methods will be used to assess microbial diversity. The intestinal immune system response will be examined using digital image analysis where primarily immunohistochemistry procedures for CD3, CD8, CD20 and CD68 immune cell markers will be performed. Thereafter, the count, density and distribution of immunocompetent cells in epithelial and stromal tissue compartments will be evaluated using AI-based platform. The interaction between the microbial shifts and intestinal immune system response in adenoma-carcinoma sequence and the healthy patients will be examined. In addition, fecal samples will be explored for gut microbiota’s composition, comparing fecal- and tissue-derived bacterial patterns in healthy gut and along the adenoma-carcinoma sequence.DiscussionWe hypothesize that changes within the human gut microbiota led to detectable alterations of the local immune response and correlate with the progression from normal mucosa to colorectal adenoma and invasive carcinoma. It is expectable to find more severe gut immune infiltration at dysplasia site, though analyzing invasive colorectal cancer we expect to detect broader mucosa-associated and luminal microbiota changes with subsequent local immune response at near-lesion site and possibly throughout the entire colon. We believe that specific compositional differences detected around premalignant colorectal lesions are critically important for its primary role in initiation and acceleration of colorectal carcinogenesis. Thus, these microbial patterns could potentially supplement fecal immunohistochemical tests for the early non-invasive detection of colorectal adenoma. Moreover, AI-based analysis of immune infiltrates could become additional diagnostic and prognostic tool in precancerous lesions prior to the development of colorectal cancer.RegistrationThe study is registered at the Australian New Zealand Clinical Trials Registry (ACTRN12624000976583) https://www.anzctr.org.au/.